Truth is fragmentary travelogues & diaries - Bell, Gabrielle 1976- (Uncivilized Books, 2014)
A collection of comic diaries kept by the author between 2010-2013 when attending various comic festivals
Keywords: Comic books, strips, etc / United States; Travelogues -- Comic books, strips, etc; USA; Comic; Tagebuch; Autobiografie